The Perception of Older Generation Y on Luxury and Luxury Brands: An Exploratory Study - Suvarnasuddhi, Sarisa (2007)
Luxury is usually associated with the finer things in life. Everyone wants a bit of luxury. It is a concept that is used often but no one really understands what it actually means. Considering the amount of profit the luxury market reaps in annually, the drivers behind this should be looked at. The consumers of luxury brands include both young and old consumers. In order to understand the influx of young consumers in the luxury market, an understanding has to be made into how it originated. This study explores consumer perception further by dealing with aspects of luxury and luxury brands within the older Generation Y cohort (18-25). The existing literature on luxury are reviewed and using the framework of luxury, developed by Dubois, Czellar, and Laurent (2001), as the basis for analysis. It also incorporates aspects of consumer behavior and branding which luxury brands may influence consumer perception. Three objectives of this research are to identify the validity of the framework of luxury, investigate methods in which the older Generation Y cohort defines luxury, and the impact of brands in their perceptions. A series of in-depth interviews were conducted with nine respondents from the older Generation Y cohort. Themes arising from the research will be discussed in the results and analysis chapter. Even though the study is exploratory by nature, the study indicates the representations of the price and quality in creating the illusion of luxury. Lastly, implications in marketing and industry, and recommendations for further research are discussed in the conclusion.